P-243 Dragonfly – group work with grieving families. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Nichols, Rob; Purnell, Gemma
Abstract : Background: Dragonfly group is a St Richard's Hospice bereavement group. It supports groups of families over six evenings, two weeks apart. It is run by a small team of staff and volunteers. Over a number of years, the group has developed an effective way of helping families work through their grief. The core principles are: The most basic requirement is to give everyone a safe environment where they can express, articulate, and discuss their grief; Initially, allowing children to freely discuss their grief is easier if they are separated from their adult family members; Once children feel comfortable expressing their grief, bringing the children and adults together and continuing to provide a safe environment for them to articulate their grief together is beneficial for the whole family; Taking time doing too little is better than rushing to do too much. We have learnt that initially both children and adults are reluctant to discuss or express their grief for fear of upsetting the other. Also, we believe that children learn from others that hiding their grief is a correct response to their feelings, following the death of a loved one. To address this reluctance the following schedule of evening sessions has developed: Week 1 – An initial ice breaker where the families make pizzas together; Weeks 2 – 4 Groups are split into child and adult sessions. Exercises around craft and fun are used to allow the children to describe and discuss their feelings. The adults discuss their feeling within their group with some simple exercises being used to encourage discussion; Weeks 5 – 6 The families are brought back together, where they express and discuss their feelings of grief together in an environment where they feel safe to do so.